The effect of sung speech on socio-communicative responsiveness in children with autism spectrum disorders - Paul, Arkoprovo; Sharda, Megha; Menon, Soumini; Arora, Iti; Kansal, Nayantara; Arora, Kavita; Singh, Nandini C. (Frontiers in Human Neuroscience, 2015)
There is emerging evidence to demonstrate the efficacy of music based interventions for improving social functioning in children with Autism Spectrum Disorders (ASD). While this evidence lends some support in favour of using song over spoken directives in facilitating engagement and receptive intervention in ASD, there has been little research that has investigated the efficacy of such stimuli on socio-communicative responsiveness measures. Here, we present preliminary results from a pilot study which tested whether sung instruction, as compared to spoken directives, could elicit greater number of socio-communicative behaviours in young children with ASD. Using an adapted single-subject design, three children between the ages of 3 and 4 years, participated in a programme consisting of 18 sessions, of which 9 were delivered with spoken directives and 9 with sung. Sessions were counterbalanced and randomized for three play activities - block matching, picture matching and clay play. All sessions were video-recorded for post-hoc observational coding of three behavioural metrics which included performance, frequency of social gesture and eye contact. Analysis of the videos by two independent raters indicated increased socio-communicative responsiveness in terms of frequency of social gesture as well as eye contact during sung compared to spoken conditions across all participants. Our findings suggest that sung directives may play a useful role in engaging children with ASD and also serve as an effective interventional medium to enhance socio-communicative responsiveness.